Fault detection and diagnosis using robust transition structures - Sánchez, Betsy; Rojas, Rubén (Revista Técnica da Faculdade de Engenharia da de Zulia)
The robust transition structures originally applied to control processes with different operation points, is presented as alternative for fault detection and diagnosis. An advantage of this method is the reduction of the mathematical complexity inherent to many structures applied to fault detection and diagnosis. The proposed method utilizes parametric mathematical models to characterize the faults in the instruments. Finally, this scheme is tested by means of computer simulations through a Continuous Stirred tank Reactor (CSTR) model as a process.